THE INFLUENCE OF INFLATION, INTEREST RATES AND EXCHANGE RATES ON STOCK PRICES (STUDY ON: PT SENTUL CITY TBK. IN PROPERTY AND REAL ESTATE SECTOR COMPANIES LISTED ON THE IDX) - Rico Nur Ilham; Siti Zahara; Juliyanti; Mia Claudia; Silvia Wulandari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Globalization has a fairly broad impact on investment and funding, both short term and long term funding. Investment and funding can make it easier for companies to get additional sources of capital for the company's operational activities. Stocks are the instrument that many investors choose because stocks are able to provide an attractive profit rate and by issuing shares is one of the company's choices when deciding to fund the company. Prospective investors need to pay attention to stock price developments or share profit rates as well as macroeconomic factors that affect stock prices in order to reduce the risk of loss in investment activities in the capital market. From the examination it can be seen that exchange rates, inflation, and interest each have their own influence on the prices of shares listed on the Indonesia Stock Exchange. The object of this study is the price of company shares in the property and real estate sector which are listed on the Indonesian Stock Exchange. The results of the simultaneous test analysis show that there is a significant influence of inflation, the BI rate and the US dollar exchange rate simultaneously on the stock prices of property and real estate companies on the Indonesia Stock Exchange. There is no significant effect partially on the inflation variable on company stock prices in the property and real estate sector on the Indonesia Stock Exchange. There is a partial significant effect of the BI rate on stock prices of property and real estate companies on the Indonesia Stock Exchange. There is a significant effect partially on the exchange rate on stock prices of property and real estate sector companies on the Indonesia Stock Exchange.